Penerapan Media (Kahoot) untuk Meningkatkan Motivasi Siswa di Madrasah Ibtidaiyah Nurul Yaqin Simpang Sungai Duren - Indah Aura Febrian; Vioni Saputri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is based on the low motivation to learn in the Natural and Social Sciences (IPAS) learning process. The purpose of this study is to increase students' motivation to learn by using kahoot media in Natural and Social Sciences subjects in class V CMadrasah Ibtidaiyah Nurul Yaqin Simpang Sungai Duren. This type of research is Classroom Action Research (PTK). Data collection techniques are carried out by means of interviews, tests, observations and documentation. The subject of this research is students of class V C. This research was carried out in semester 2 of the 2024/2025 school year. The results of this study show that using kahoot media can increase the learning motivation of students in Natural and Social Sciences class V C. Details of the results of students' observations using kahoot media have increased from cycle I with an average score of 63.35% can be categorized as poor and in cycle II it increased to 80.10% with a good category. It was concluded that using kahoot media can increase student motivation in the Natural and Social Sciences subject class V C Madrasah Ibtidaiyah Nurul Yaqin Simpang Sungai Duren..